2018
DOI: 10.15446/profile.v20n1.63323
|View full text |Cite
|
Sign up to set email alerts
|

Colombian English Teachers’ Professional Development: The Case of Master Programs

Abstract: Master degree programs have rapidly increased in Colombia to the point where they are one of the most favored options for English teachers seeking to bolster their professional development. This survey study characterizes eighty participants, their five master programs, and their perceptions concerning the influence these graduate courses exerted on their teaching. While participants' pedagogical and research work seemed to have benefited the most from their studies, their practices involving language policy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…E nglish Language Teaching (ELT) Master's in Colombia arose from the needs of the educational sector to respond to the demands of social and economic development. This explains why from 2000 to 2016 the number of ELT Masters increased from two to 14 (Viáfara & Largo, 2018). For these authors, "MA graduates and candidates asserted that increasing of conceptual frameworks supported different features of their practices as they gained clarity about the teaching and learning processes and re-shaped their pedagogical actions" (p. 110).…”
Section: No 22mentioning
confidence: 99%
See 2 more Smart Citations
“…E nglish Language Teaching (ELT) Master's in Colombia arose from the needs of the educational sector to respond to the demands of social and economic development. This explains why from 2000 to 2016 the number of ELT Masters increased from two to 14 (Viáfara & Largo, 2018). For these authors, "MA graduates and candidates asserted that increasing of conceptual frameworks supported different features of their practices as they gained clarity about the teaching and learning processes and re-shaped their pedagogical actions" (p. 110).…”
Section: No 22mentioning
confidence: 99%
“…In this section, we made three assumptions: a) MA programs represent one of the most important sources of professional development (Villegas-Reimers, 2003;Truscott de Mejía, 2016;Viáfara & Largo, 2018;Buendía & Macías, 2019), b) reflection is a sine qua non condition in continued teacher education (Hernández, 2015;Viáfara & Largo, 2018;Nuñez & Tellez, 2015), and c) curriculum design and implementation is the materialization of teaching initiatives and skills that translate in enhanced teaching practices (Graves, 2000;Nunan,1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other considerations by such as individual and social perspectives of learning and teaching, post-method approaches, creation of knowledge in school and social settings, and promotion of meaningful practices among teachers are, nonetheless, worthy of inclusion in the design of teacher development programs. Viáfara and Largo (2018) reported that postgraduate programs, teachers' number one option for continuing their preparation, facilitate teachers' analysis of educational policies, their reflective skills, and curricular knowledge. More awareness of the relevance of doing classroom research to innovate, and the feeling of empowerment to be able to adjust institutional educational policies were other relevant findings in this study.…”
Section: Author and Yearmentioning
confidence: 99%
“…Such a road will consequently lead them to a successful transformation in both their own learning and teaching. Secondly, teachers need to be prepared to face the challenges of contemporary education by shifting from obsolete and outdated ways of teaching to the design and development of more inclusive learning environments; tailored assessment systems and also through the strengthening of their professional skills (Viáfara & Largo, 2018). Finally, we believe that the triad comprising of systematic reflection, learner-centeredness, and self-regulation leads to the dynamization of the learning and teaching practices of the language classroom and also constitute the pillars (we believe) that are necessary to respond to the needs of contemporary professionals (see Figure 2).…”
Section: On the Road To Self-regulation: Gauging Pivotal Change In Thmentioning
confidence: 99%